The earth that modernism built empire and the rise of planetary design - Cupers, Kenny 1977- (University of Texas Press, 2024)
"In The Earth That Modernism Built, architectural historian Kenny Cupers provides an intellectual history of the relationship between modernism and the project of colonial settlement in the context of Wilhelmine and Weimar Germany. In particular, he explores the ways that early twentieth-century modernist architects transposed nineteenth-century ideas from realms such as biology and soil research into the analysis and design of spatial, aesthetic, social, and technical arrangements. The key concept for much of his discussion is Bodenständigkeit--earth-boundedness or rootedness in the soil. The project of making buildings look as if they were bound to the earth was not just a matter of aesthetics, he argues, but came to serve in efforts to define what and who was natural, who belonged and who did not [...]."
Keywords: Geschichte 1880-1930; Umweltgestaltung; Moderne; Imperialismus; Architektur; Deutschland; Architecture, Colonial / Political aspects / Germany / History; Imperialism and architecture / Germany / History; Settler colonialism / Germany / Philosophy / History; Modern movement (Architecture) / Political aspects / Germany / History; Modern movement (Architecture) / Philosophy / History; Modern movement (Architecture) / Social aspects / Germany / History; Architectural design / Germany / Philosophy / History; Germany / Colonies / History; Architecture coloniale / Aspect politique / Allemagne / Histoire; Impérialisme et architecture / Allemagne / Histoire; Colonialisme de peuplement / Allemagne / Philosophie / Histoire; Mouvement moderne (Architecture) / Aspect politique / Allemagne / Histoire; Mouvement moderne (Architecture) / Philosophie / Histoire; Mouvement moderne (Architecture) / Aspect social / Allemagne / Histoire; Design architectural / Allemagne / Philosophie / Histoire; Architectural design / Philosophy; German colonies; Imperialism and architecture; Germany; History